2018
DOI: 10.1007/s40273-018-0745-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Niraparib Versus Routine Surveillance, Olaparib and Rucaparib for the Maintenance Treatment of Patients with Ovarian Cancer in the United States

Abstract: Objectives The aim was to evaluate the cost-effectiveness of niraparib compared with routine surveillance (RS), olaparib and rucaparib for the maintenance treatment of patients with recurrent ovarian cancer (OC). Methods A decision-analytic model estimated the cost per quality-adjusted life-year (QALY) gained for niraparib versus RS, olaparib, and rucaparib from a US payer perspective. The model considered recurrent OC patients with or without germline BRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 28 publications
2
71
0
Order By: Relevance
“…This trend was consistent in the abstracts we reviewed but did not score; of the abstracts assessed, two studies included a longer time horizon, with the remaining studies focused on shorter time horizons [18,25]. Only 3 of 18 studies reported discounting outcomes, with two studies reporting a 3% discounting rate and one study reporting a 3.5% discounting rate (QHES item 8) [18,22,25]. All full-text studies met QHES items 4 and 6 (incremental analysis between alternatives).…”
Section: Objective Perspective Subgroups and Time Horizon For Costsupporting
confidence: 53%
See 4 more Smart Citations
“…This trend was consistent in the abstracts we reviewed but did not score; of the abstracts assessed, two studies included a longer time horizon, with the remaining studies focused on shorter time horizons [18,25]. Only 3 of 18 studies reported discounting outcomes, with two studies reporting a 3% discounting rate and one study reporting a 3.5% discounting rate (QHES item 8) [18,22,25]. All full-text studies met QHES items 4 and 6 (incremental analysis between alternatives).…”
Section: Objective Perspective Subgroups and Time Horizon For Costsupporting
confidence: 53%
“…1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Five of the 18 studies were published as full-text articles [17,19,22,26,33] and the remaining were abstracts presented at conferences. The 18 studies identified by the systematic literature review and the key elements of their study designs are summarized in Table 1.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations